Feasibility of Macroporous CeO2 Photocatalysts for Removal of Lead Ions from Water - Takuya Nozaki; Ryo Shoji; Yasukazu Kobayashi; Kazunori Sato (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
Removal of lead ions from water was conducted by a coupling approach of adsorption and photoelectrodeposition over a macroporous CeO2 photocatalyst loaded with ZnO. The photocatalyst was prepared by the hard template method and the impregnation method. The various size of silica spheres (0.05-0.4 µm) were used as a template for the photocatalyst, and the highest BET surface area (73.8 m2/g) was given in the sample prepared with the smallest silica sphere (0.05 µm). In the removal of lead ions, the porous sample showed a large amount of removal of lead ions. In addition, the ZnO loaded catalysts showed a larger amount of removal for lead ions than an unloaded catalyst under the UV light irradiation. In the reaction, since zinc ions were simultaneously dissolved to the solution, it was suggested that this reaction was the ion-exchange reaction between lead ions and zinc ions and was promoted by the UV light irradiation.